Prognostic significance of IL-33 and ST2 expression in head and neck squamous cell carcinoma: a systematic review - Acharya, Swetha; Hegde, Usha; Acharya, Anirudh Balakrishna; Madhunapantula, SubbaRao V.; Sreeshyla, Huchanahalli Sheshanna; Nitin, Priyanka; Karnik, Medha (Frontiers in Oral Health, 2025)
BackgroundInterleukin-33 (IL-33) and Suppression of tumorigenicity 2 (ST2) expression are strongly associated with tumor growth and progression in diverse cancers, indicating the possibility of targeting the IL-33/ST2 axis pathway as a favorable therapeutic approach. However, the specific implications of IL-33/ST2 expression in Head and Neck Squamous Cell Carcinoma (HNSCC) prognosis are not fully understood. Thus, there is a need for more comprehensive research to verify the tasks and clinical significance of IL-33 and ST2 in HNSCC.ObjectivesThe objective of this study was to evaluate the potential of differentially expressed IL-33 and ST2 in tumor tissues that could serve as novel biomarkers in HNSCC.Material & methodsThe Web of Science, Scopus, and PubMed electronic databases were searched and analyzed from January 2013 to July 2023.ResultsNine studies fulfilling the inclusion criteria were analyzed. These selected studies were mainly having observational analytical study design, predominantly conducted within the Southeast Asian population. IL-33, primarily located in the stroma, demonstrates enhanced expression within carcinoma-associated fibroblasts (CAFs). Overexpression of IL-33 in CAFs correlates with its expression in tumor cells, as per some of these reports. Elevated IL-33 levels in CAFs are associated with unfavorable clinical outcomes. Increased IL-33 expression is related to poor nodal metastasis-free survival, indicating an adverse prognosis in HNSCC. In HNSCC, tumor cells and regulatory T cells (Tregs) expressed ST2. The degree of ST2 expression on Tregs corresponds to the abundance of IL-33 expressing CAFs. IL-33 increases the Tregs density and amplifies their suppressive capability. Poorer survival outcomes in HNSCC are linked to elevated ST2 expression in Tregs combined with the existence of IL-33-expressing CAFs.ConclusionCAF-driven cancer invasiveness relies on IL-33 signaling via paracrine and autocrine pathways. IL-33 may be a prognostic biomarker and therapeutic target, aiming to improve prognosis and survival in HNSCC. The IL-33/ST2 axis significantly configures the tumor microenvironment and tumor aggressiveness in HNSCC. The role of serum IL33 and ST2 remains to be further studied in HNSCC.Systematic Review Registrationhttps://www.crd.york.ac.uk/PROSPERO/i, identifier (CRD42023447963).